Some Helminth Parasites of Gharial from Chitwan National Park, Nepal - Kumal, Prakash Mani; Maharjan, Mahendra (Nepal Journal of Science and Technology, 2015)
A study on helminth parasites on captive gharial (Gavialis gangeticus) was conducted during July-December 2012 at Gharial Breeding Centre, Kasara, Chitwan National Park to isolate, identify and find out their prevalence. Dead gharial hatchlings were collected directly from the centre in fresh and frozen conditions. Out of 85 samples examined, 40 samples 47.06% as prevalence rate of helminth parasites. During the study three helminth parasites were first reported from the gharials of Nepal; Pentastomid (Sebekia sp.), Capillarioids and Ascaridoids. The dead hatchlings were found to be infected with Pentastomid (41.17%), Ascaridoids (7.05%), Capillarioids (1.17%), Proctocaecum gairhei (3.52%) and Exotidendrium sp. (36.47%). In the month of December helminth parasites showed highest prevalence; Sebekia sp. (100%) and Proctocaecum gairhei (75%) and Exotidendrium sp. (100%) and the lowest prevalence in the month of July; Sebekia sp. (4%), Capillarioids (4%) and Exotidendrium sp. (8%). DOI: http://dx.doi.org/njst.v15i2.12111 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 37-40